Clinical manifestations of the anti-IgLON5 disease. (2nd May 2017) - Gaig, Carles; Graus, Francesc; Compta, Yarko; Högl, Birgit; Bataller, Luis; Brüggemann, Norbert; Giordana, Caroline; Heidbreder, Anna; Kotschet, Katya; Lewerenz, Jan; Macher, Stefan; Martí, Maria J.; et al.
Abstract : Objective: To report the presentation, main syndromes, human leukocyte antigen (HLA) association, and immunoglobulin G (IgG) subclass in the anti-IgLON5 disease: a disorder with parasomnias, sleep apnea, and IgLON5 antibodies. Methods: This was a retrospective clinical analysis of 22 patients. The IgG subclass was determined using reported techniques. Results: Patients' median age was 64 years (range 46–83). Symptoms that led to initial consultation included sleep problems (8 patients; 36%), gait abnormalities (8; 36%), bulbar dysfunction (3; 14%), chorea (2; 9%), and cognitive decline (1; 5%). By the time of diagnosis of the disorder, 4 syndromes were identified: (1) a sleep disorder with parasomnia and sleep breathing difficulty in 8 (36%) patients; (2) a bulbar syndrome including dysphagia, sialorrhea, stridor, or acute respiratory insufficiency in 6 (27%); (3) a syndrome resembling progressive supranuclear palsy (PSP-like) in 5 (23%); and (4) cognitive decline with or without chorea in 3 (14%). All patients eventually developed parasomnia, sleep apnea, insomnia, or excessive daytime sleepiness. HLA-DRB1*10:01 and HLA-DQB1*05:01 were positive in 13/15 (87%) patients; the DRB1*10:01 allele was 36 times more prevalent than in the general population. Among 16 patients with paired serum and CSF samples, 14 had IgLON5 antibodies in both, and 2 only in serum (both had a PSP-like syndrome). Twenty of 21 patients had IgG1 and IgG4 antibodies; the latter predominated in 16. Conclusions: Patients with IgLON5 antibodies develop a characteristic sleep disorder preceded or accompanied by bulbar symptoms, gait abnormalities, oculomotor problems, and, less frequently, cognitive decline. IgG4 subclass antibodies predominate over IgG1; we confirm a strong association with the HLA-DRB1*10:01 allele.